Metallschäume Herstellung, Eigenschaften, Potenziale und Forschungsansätze – mit Schwerpunkt auf Aluminiumschäume - Lange, Günther 1967- (De Gruyter, 2020)
Metal foams – especially aluminum foams – are seen today as belonging to the class of porous metals. The book provides an overview of the different production options, properties, and current applications, including the most recent research themes on open-celled and closed-celled metal foams
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jun 2020)
Keywords: Aluminiumsschäume; Material properties; Materialwissenschaften; Metall; Poröse Metalle; aluminum foam; metals; porous metals; Technology & Engineering / Materials Science / General; Schaumaluminium; Metallschaum